The critical situation and its relation with the performance of the basic skills in the artistic gymnastic for woman - Adnan, Ban (Journal of Physical Education, 2014)
The importance of the research lies in that the critical situation which is considered as a psychological phenomenon, may affect the performance of the girl- student while doing their artistic gymnastics skill. the problem is that there are many artistic gymnastic devices and there are some difficulties when movements are performed on them. the student is submitted to rules and structures regarding the skill for each device where the student feels embarrassed and fear of failure. this is what is called the critical situation which may be reflected negative on the students final performance. the aim of the research is acknowledging the relationship between the critical situation and the performance of some of the basic of the artistic gymnastics skill s for women. the purpose of the research is to insist on this statistical relationship. the methodology of the research،the number of the sample which is (40) students and the critical situation have been mentioned. After the means of statistics has been used, the results have proved there is strong relationship between the critical situation and the level of the performance. the researcher has recommended the necessity of using critical situation measures periodically to make benefits from these results which are given by these measurements.